Impact of foreign direct investment volatility on economic growth of asean-5 countries - Venus, Khim-Sen Liew; Choong, Chee-Keong (Economics Bulletin, 2009)
This study examines the impact of volatility of FDI, rather than its level on the economic growth of ASEAN-5 countries. Using bounds testing approach, we show that FDI volatility retards long-run economic growth in Indonesia, Malaysia, the Philippines and Thailand. Our results suggest that the economic growth of Indonesia is the most susceptible to the adverse effect of FDI volatility. These findings, which are robust to different measures of FDI volatility, are of concern in dealing with the economic growth of developing countries in the ASEAN region, which rely heavily on FDI.